2007
DOI: 10.1172/jci29919
|View full text |Cite
|
Sign up to set email alerts
|

Critical roles for CCR2 and MCP-3 in monocyte mobilization from bone marrow and recruitment to inflammatory sites

Abstract: Monocyte recruitment to sites of inflammation is regulated by members of the chemokine family of chemotactic cytokines. However, the mechanisms that govern the migration of monocytes from bone marrow to blood and from blood to inflamed tissues are not well understood. Here we report that CC chemokine receptor 2 (CCR2) is highly expressed on a subpopulation of blood monocytes whose numbers are markedly decreased in CCR2 -/-mice. In bone marrow, however, CCR2 -/-mice had an increased number of monocytes, suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

60
886
2
7

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 950 publications
(955 citation statements)
references
References 35 publications
(39 reference statements)
60
886
2
7
Order By: Relevance
“…However, CCR2 and CXCR2 are important in mobilizing monocytes and neutrophils, respectively, from the bone marrow [7,8,35], which complicates deciphering the role of these chemokine receptors for subsequent recruitment to tissues. In support of this, Serbina and Pamer showed that CCR2 is not required for monocyte migration into infected spleen or inflamed peritoneum [7] while Tsou et al found that early, but not late phase, monocyte recruitment to the peritoneum is CCR2-dependent [9]. Thus, very refined studies are required to directly assess the role of CCR2 for migration from blood into inflamed tissues during oral Salmonella infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, CCR2 and CXCR2 are important in mobilizing monocytes and neutrophils, respectively, from the bone marrow [7,8,35], which complicates deciphering the role of these chemokine receptors for subsequent recruitment to tissues. In support of this, Serbina and Pamer showed that CCR2 is not required for monocyte migration into infected spleen or inflamed peritoneum [7] while Tsou et al found that early, but not late phase, monocyte recruitment to the peritoneum is CCR2-dependent [9]. Thus, very refined studies are required to directly assess the role of CCR2 for migration from blood into inflamed tissues during oral Salmonella infection.…”
Section: Discussionmentioning
confidence: 99%
“…39: 3019-3030 DOI 10.1002 Immunity to infection 3019 marrow into the blood during steady state and infection [7][8][9][10]. They are also central for monocyte and neutrophil recruitment and host survival during infections [9,[11][12][13][14][15][16]. Despite the undisputed role of chemokine receptors and their ligands in ensuring survival to infection, it is difficult to assess the role of individual chemokines in phagocyte recruitment, particularly in the complex environment of bacterial-infected tissues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While monocytes are also formed in the liver and spleen [70][71][72], the view that monocytes are derived from the bone marrow has been established since the early 1960s and still dominates [73]. The monocytes produced from the bone marrow exit to the circulatory system in a C-C chemokine receptor 2 (CCR2)-dependent manner and enter tissues to give rise to tissue macrophages [74]. Circulating monocytes possess 2 distinct phenotypes with unique functional properties in human and mice.…”
Section: Monocytes and Monocyte-derived Macrophagesmentioning
confidence: 99%
“…Leur devenir dépend de leur phénotype, d'une part, et du microenvironnement dans lequel elles vont se diffé-rencier en macrophages, d'autre part. Chez la souris, les monocytes Gr1 + Ly-6C high , équivalents des monocytes classiques CD14 + CD16 -chez l'homme, seraient les précurseurs des macrophages pro-inflammatoires du tissu adipeux [18,19]. Chez l'homme, des premiers travaux ont révélé que les cellules mononucléées circulantes expriment un statut pro-inflammatoire chez les sujets obèses [20].…”
Section: D'où Viennent Les Macrophages Du Tissu Adipeux ?unclassified